Evaluation of Educational Supervisors’ Opinions about Families’ Contribution to Education Costs - Hüseyin Yolcu; Bostanci, Aynur B. (My University, 2013)
This paper which aims to display the opinions of educational supervisors about families’ contribution to education costs is a descriptive study of survey models. In the study, a qualitative research design was used. A workgroup consisting 14 educational supervisors working in Uºak and Kastamonu cities was formed according to simple random sampling method which is among the purposeful sampling techniques. Data for the study was collected using semi-structured interview techniques. Results of the study can be explained like this. A large number of the educational supervisors chosen for the study define ‘the right of education’ as a normative definition. According to educational supervisors, deficient public sources, schools’ having no special budgets and families’ attaching importance to their children’s education requires a family contribution for education costs. Also, a significant number of the educational supervisors think it is necessary for families to contribute to education costs in terms of more well-qualified education, acceptance of schools and equal sharing of the costs. Moreover, among the educational supervisors, there is some thinking that families’ contribution to educational costs can bring about a social justice problem by increasing the inequality of opportunity and capability among the different segments of the society. Educational supervisors can face variety of complaints or demands about the topic which are expressed by families and teachers in the process of school supervision.
Keywords: Educational supervisor, school expenditure, education costs, families’ contribute to education costs, school; 4. Education